IMMUNE STATE AND LYMPHOCYTE-TO-PLATELET ADHESION IN CHILDREN WITH CHRONIC DEFORMING BRONCHITIS AND BRONCHIECTASIA - B. I. Kuznik; B. Ts. Batozghargalova; Yu. A. Vitkovsky (Медицинская иммунология, 2014)
Abstract. Thirty-seven children (7 to 14 years old) with chronic inflammatory lung diseases (ILD) were under study. It was revealed that the contents of T-lymphocytes with CD3+ and CD4+ markers, and B-lymphocytes (CD20+) were relatively decreased in the patients, but their absolute amounts proved to be increased, along with sufficiently decreased CD4+/CD8+ ratio, and diminished IgA, IgG and IgM concentrations. The numbers of lymphocyte able to adhere to platelets was relatively decreased, being, however, increased in absolute counts. In the patients with ILD, we have found increased levels of IL-1β, IL-8, TNFα, IFNα, IFNγ. The lymphocyte-to-platelet adherence is an objective test that reflects functional state of cell immunity. (Med. Immunol., vol. 10, N 6, pp 583-588).